The External Impact of PTPN 1 Regional 5 Mumbul Jember Plantation from a Sharia Economic Perspective - Citra Putri Oktavia; Putri Catur Ayu Lestari (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
The agro-industry, or industry that uses agricultural products as raw materials, has successfully recorded growth of 5.20% and contributed up to 8.89% to the national Gross Domestic Product (GDP) in 2024. This underscores the importance of the agro-industry sector in the country's economic framework, particularly through the contribution of the non-oil and gas processing sector which reached 51.81%. This study aims to analyze the externality impacts caused by the activities of PTPN 1 Regional 5 Kebun Mumbul Jember on surrounding communities and examine these impacts from the perspective of Islamic economics. PTPN 1 Regional 5 Kebun Mumbul is a plantation unit managing sugarcane commodities and directly interacting with local communities. This research uses a qualitative descriptive approach. Data were collected through observation, interviews, documentation, and literature study. Informants were determined using purposive sampling, while data validity was tested using source and technique triangulation. The results show that the activities of PTPN 1 Regional 5 Kebun Mumbul generate both positive and negative externalities. Positive externalities include employment opportunities, development of local businesses, and social assistance programs through Corporate Social Responsibility and Partnership and Community Development Programs. Meanwhile, negative externalities include potential environmental disturbances due to suboptimal waste management. From the perspective of Islamic economics, these activities are aligned with the principles of tawhid, justice, and public welfare, although environmental management still needs improvement to support sustainable economic activities.